Differences in number and distribution of striatal calbindin medium spiny neurons between a vocal-learner (Melopsittacus undulatus) and a non-vocal learner bird (Colinus virginianus) - Garcia-Calero, Elena; Bahamonde, Olga; Martinez, Salvador (Frontiers in Neuroanatomy, 2013)
Striatal projecting neurons, known as medium spiny neurons (MSNs), segregate into two compartments called matrix and striosome in the mammalian striatum. The matrix domain is characterized by the presence of calbindin immunopositive (CB+) MSNs, not observed in the striosome subdivision. The existence of a similar CB+ MSN population has recently been described in two striatal structures in male zebra finch (a vocal learner bird): the striatal capsule and the Area X, a nucleus implicated in song learning. Female zebra finches show a similar pattern of CB+ MSNs than males in the developing striatum but loose these cells in juveniles and adult stages. In the present work we analyzed the existence and allocation of CB+MSNs in the striatal domain of the vocal learner bird budgerigar (representative of psittaciformes order) and the non-vocal learner bird quail (representative of galliformes order). We studied the co-localization of CB protein with FoxP1, a transcription factor expressed in vertebrate striatal MSNs. We observed CB+ MSNs in the medial striatal domain of adult male and female budgerigars, although this cell type was missing in the potentially homologous nucleus for Area X in budgerigar. In quail, we observed CB+ cells in the striatal domain at developmental and adult stages but they did not co-localize with the MSN marker FoxP1. We also described the existence of the CB+ striatal capsule in budgerigar and quail and compared these results with the CB+ striatal capsule observed in juvenile zebra finches. Together, these results point out important differences in CB+MSN distribution between two representative species of vocal learner and non-vocal learner avian orders (respectively the budgerigar and the quail), but also between close vocal learner bird families.